Investigasi Efek Partial Shading Terhadap Daya Keluaran Sel Surya - Bandiyah Sri Aprillia; Muhammad Rafiqy Zulfahmi; Achmad Rizal (Politeknik Caltex Riau, 2019)
The electrical energy of solar power plants which integrated into the networks depends on the intensity of solar radiation. However, some solar power plant areas there are still present trees and buildings around it that can partially cover the surface area of ​​the solar panel (partial shading). This study aims to investigate the effects of solar radiation variability due to several partial shading conditions on the 1 Wp solar cell output power. Based on observations from 10:00 to 14:00, the open-circuit voltage and short circuit current in solar cells decreases with increasing intensity of partial shading. The greater the partial shading of the solar cell, the lower the power output will be. The half partial shading effect of the total solar cell area resulted in a power reduction of 88.2%. A quarter of shading causes a decrease in the output power of solar cells by 75.6% compared to the power output under normal conditions. In addition, the increase in the temperature of solar cells resulted in a significant decrease in the open-circuit voltage.